Informational Educational Programs on Adolescent Health - Sittoova Mariyam Amangildievna (Genius Journals, 2023)
Positive quantitative characteristics of teenagers are accompanied by a sharp transformation of moral and ethical values that have occurred in modern society, which has led to a change in attitudes towards adolescent health and adolescent behavior
Keywords: Moral and ethical; transformation; case technology; substance abuse